Anxiety, depression symptoms, and psychological resilience among hospitalized COVID‐19 patients in isolation: A study from Wuhan, China - Li Chen; Zhenmeng Wang; Dan Liu; Dandan He; Shulin Du; Zezhi Li; Shuyun Li; Yuehong Sheng (Brain and Behavior, 2023)
Abstract Objective To investigate the status of anxiety, depression, and psychological resilience among individuals with COVID‐19, and their interrelationships to provide a scientific basis for developing psychological intervention strategies for these patients. Methods A total of 126 patients with COVID‐19 who were admitted to Wuhan Huoshenshan Hospital were recruited in this study. A comprehensive survey was conducted using a general information questionnaire, the Self‐Rating Anxiety Scale, the self‐rating depression scale, and the Chinese version of the psychological Connor–Davidson resilience scale; a questionnaire‐based survey was conducted. Results Significant differences in anxiety scores were observed among COVID‐19 patients with different education levels and the number of immediate family members. The differences in depression scores were noted among patients of different age groups, and marital statuses were also significant. The total psychological resilience score and the scores of all dimensions are negatively correlated with anxiety and depression. Furthermore, the patient's gender, the number of immediate family members, and the psychological resilience dimensions are associated with the severity anxiety of patients. Patient age and psychological resilience are associated with the depression level of patients. Conclusion Patients with COVID‐19 exhibit elevated levels of both anxiety and depression. Notably, psychological resilience emerges as a protective factor against the development of anxiety and depression.